Health Care Seeking Behaviour For Chronic Morbidity Among The Aged In New Juaben Municipality - Kpesese, V.K. (University of Ghana, 2014)
While most societies undergoing epidemiological and demographic transitions experience increase in number and proportion of the aged, we have unfortunately observed the reverse in the New Juaben Municipality between 2000 (13.2 per cent) and 2010 (7.3 per cent) (GSS, 2012). This coupled with high prevalence of some chronic diseases among the aged with poor access to professional or formal health care services in the study area (Britwum et al, 2013. This study was therefore designed to describe health care seeking behaviour for chronic morbidity among the aged and factors associated with it in the study area. The study recruited individuals aged 60 years and above with at least 3 months of signs or symptoms of chronic conditions or diagnosed medically of at least a chronic condition as respondents. We captured the various health care seeking behaviours for chronic conditions at first, second and third lines as against their self-rated health status and type of financing for them. We also appraised their last health care seeking behaviour prior to the interview for health systems responsiveness using WHO dimensions of dignity, autonomy, confidentiality, prompt attention, choice, communication and basic amenities using a closed ended questionnaire. The results showed that there was no association between self-rated health status of the aged in the study and their health care seeking behaviour for chronic morbidity (P˃ 0.05). It was, however, observed that there strong association between health care seeking behaviour for chronic morbidity among the aged and their type of financing the behaviour (P˂ 0.01). Indeed, this was observed at all the three lines of seeking care for a chronic condition. Health systems responsiveness conducted on the various health care seeking behaviours ranked them as follows: Professional/Formal medical systems, 54.7 per cent, Professional Herbalists, 60.9 per cent, Non-professional herbalists, 55.1 per cent, Faith healers, 52.74 per cent, Use of self-prescribed modern medicines, 62.37 per cent, Visit to pharmacies/chemical sellers for advice and treatment, 56.1 per cent, Use of self-prescribed herbal/traditional preparations, 48.5 per cent and Use of local herbs/materials on advice of family members and friends, 34.0 per cent. Type of financing health care was significantly associated (P˂0.01) with seeking the type of health care seeking behaviour to be sought by the aged for chronic morbidity in the New Juaben Municipality. Meanwhile, the Professional or formal health care seeking behaviour could be made more attractive for responsiveness if efforts are geared towards responding to the dimensions of health systems except for dignity and basic amenities in relation to its competing and complementing health systems.
Thesis (MPH)
Keywords: Health; Health Care Seeking Behaviour; Chronic Morbidity; Aged; New Juaben Municipality; Ghana